Somatotropic Axis Regulation Unravels the Differential Effects of Nutritional and Environmental Factors in Growth Performance of Marine Farmed Fishes - Pérez-Sánchez, Jaume; Simó-Mirabet, Paula; Naya-Català, Fernando; Martos-Sitcha, Juan Antonio; Perera, Erick; Bermejo-Nogales, Azucena; Benedito-Palos, Laura; Calduch-Giner, Josep Alvar (Frontiers in Endocrinology, 2018)
The Gh/Prl/Sl family has evolved differentially through evolution, resulting in varying relationships between the somatotropic axis and growth rates within and across fish species. This is due to a wide range of endogenous and exogenous factors that make this association variable throughout season and life cycle, and the present minireview aims to better define the nutritional and environmental regulation of the endocrine growth cascade over precisely defined groups of fishes, focusing on Mediterranean farmed fishes. As a result, circulating Gh and Igf-i are revitalized as reliable growth markers, with a close association with growth rates of gilthead sea bream juveniles with deficiency signs in both macro- or micro-nutrients. This, together with other regulated responses, promotes the use of Gh and Igf-i as key performance indicators of growth, aerobic scope, and nutritional condition in gilthead sea bream. Moreover, the sirtuin-energy sensors might modulate the growth-promoting action of somatotropic axis. In this scenario, transcripts of igf-i and gh receptors mirror changes in plasma Gh and Igf-i levels, with the ghr-i/ghr-ii expression ratio mostly unaltered over season. However, this ratio is nutritionally regulated, and enriched plant-based diets or diets with specific nutrient deficiencies downregulate hepatic ghr-i, decreasing the ghr-i/ghr-ii ratio. The same trend, due to a ghr-ii increase, is found in skeletal muscle, whereas impaired growth during overwintering is related to increase in the ghr-i/ghr-ii and igf-ii/igf-i ratios in liver and skeletal muscle, respectively. Overall, expression of insulin receptors and igf receptors is less regulated, though the expression quotient is especially high in the liver and muscle of sea bream. Nutritional and environmental regulation of the full Igf binding protein 1–6 repertoire remains to be understood. However, tissue-specific expression profiling highlights an enhanced and nutritionally regulated expression of the igfbp-1/-2/-4 clade in liver, whereas the igfbp-3/-5/-6 clade is overexpressed and regulated in skeletal muscle. The somatotropic axis is, therefore, highly informative of a wide-range of growth-disturbing and stressful stimuli, and multivariate analysis supports its use as a reliable toolset for the assessment of growth potentiality and nutrient deficiencies and requirements, especially in combination with selected panels of other nutritionally regulated metabolic biomarkers.